Myositis interstitial lung disease and autoantibodies - Chaudhry, Shire; Christopher-Stine, Lisa (Frontiers in Medicine, 2023)
The aim of this review is to examine and evaluate published literature associated with idiopathic inflammatory myopathies (IIM) and interstitial lung disease (ILD) based on myositis specific autoantibodies (MSA) and the potential clinical significance of each autoantibody subtype for the practicing clinician. The review is a comprehensive search of literature published in PubMed from the year 2005 and onward coinciding with the surge in the discovery of new MSAs. Additionally, we comment on recommended multidisciplinary longitudinal care practices for patients with IIM-ILD with regard to imaging and other testing. Treatment is not covered in this review.